Insights into micro-and nano-zero valent iron materials : synthesis methods and multifaceted applications - Murtala, Namakka; Md Rezaur, Rahman; Khairul Anwar, Mohamad Said; Adamu, Muhammad (the Royal Society of Chemistry, 2024)
The growing threat of environmental pollution to global environmental health necessitates a focus on the search for sustainable wastewater remediation materials coupled with innovative remediation strategies. Nano and micro zero-valent iron materials have attracted substantial researchers' attention due to their distinct physiochemical properties. This review article delves into novel micro- and nano-zero valent iron (ZVI) materials, analysing their synthesis methods, and exploring their multifaceted potential as a powerful tool for environmental remediation. This analysis contributes to the ongoing search of effective solutions for environmental remediation. Synthesis techniques are analysed based on their efficacy, scalability, and environmental impact, providing insights into existing methodologies, current challenges, and future directions for optimisation. Factors influencing ZVI materials' physicochemical properties and multifunctional engineering applications, including their role in wastewater and soil remediation, are highlighted. Environmental concerns, pros and cons, and the potential industrial applications of these materials are also discussed, accenting the importance of understanding the synthesis methods, materials' applications and their impacts on humans and the environment. The review is designed to provide insights into nano-and micro-ZVI materials, and their potential engineering applications, as well as guide researchers in the choice of ZVI materials' synthesis methods from a variety of nanoparticle synthesis strategies fostering nexus between these methods and industrial applications.